Analisis Loyalitas Pelanggan Terkait Kualitas, Harga dan Desain Produk serta Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada Pengguna Kosmetik Brand Wardah) - Damayanti, Andi Ema; Manggabarani, Alfatih Sikki; Pusporini, Pusporini (Master of Management Diponegoro University, 2021)
This research is driven by efforts aimed at consumer needs with the hope that consumers are satisfied and will make repeat purchases. This research aims to determine theeinfluenceeof quality,ppriceaand product design directly or indirectly on customer loyalty through customer satisfaction as an intervening variable in purchasing cosmetics Wardah Research, this study uses 100 Wardah consumers as a sample. Sample selection using purposive sampling technique. Hypothesis testing using path analysis and bootstrap calculations as well as direct and indirect testing using structural modeling (SEM). The test results show that customer loyalty is not directly affected by product quality and price. While the design variables and customer satisfaction have a significant direct influence on customer loyalty. Then there is an indirectieffect between quality,ppriceaandpproduct design onccustomer loyalty through customer satisfaction.